External image of hypermarket as a factor of influence on consumer behavior - A. N. Timokhovich (Цифровая социология)
The set of problems of perception of elements of the external image of the organization that sells in the fast moving consumer goods (FMCG) area by the target audience has been raised. The elements of the external image of the organization that influence the behavior of hypermarket consumers are analysed. The article is based on the results of the empirical research of the hypermarket chain Globus consumer behavior. The study has been conducted using the online survey method, a sample of 658 respondents.Consumer perceptions about the company as a whole have been described, consumer attitude to the hypermarket has been revealed, the main elements of the external image of the hypermarket, on which the consumer target audience is focused on, have been defined. Insufficient involvement of consumers in events at points of sale, low awareness of different types of activities to stimulate consumers, a generally positive attitude and high brand awareness of the hypermarket have been identified. Insufficient use of the hypermarket’s website and official Internet resources by representatives of target groups (social network accounts, mobile application) has been revealed. The main channel for informing the target audience is advertising at the point of sale.Conclusions have been made about the need to develop the image policy of trade companies in the field of FMCG; about the need to promote mobile applications of hypermarkets; about the need to use interactive online technologies in social media and through the trade company`s website for operational communication with consumers, as well as to activate consumer behavior. It has been concluded about the impact of the atmosphere of a point of sale on the image of the company in the field of FMCG. Recommendations on optimizing communication channels, through which the target audience receives information about the point of sale of FMCG products, – have been developed.